Effect of lemongrass essential oil on Listeria monocytogenes gene expression. (April 2017) - Hadjilouka, Agni; Mavrogiannis, Giorgos; Mallouchos, Athanasios; Paramithiotis, Spiros; Mataragas, Marios; Drosinos, Eleftherios H.
Abstract: The aim of the present study was to assess the transcriptomic response of L. monocytogenes isolates on the exposure to lemongrass essential oil. Overnight cultures of six strains previously isolated from a strawberry sample were spread over the surface of BHI agar and exposed to 5 and 10 μL of lemongrass essential oil applied on a Whatman paper placed on the lid. Three of them survived in the former case and one in the latter; in all cases biomass was collected and RNA was isolated. The expression of the key virulence genes prfA, sigB, plcA, plcB, hly, inlA, inlB, inlC, inlJ, lmo2470 and lmo2672, as well as accA, acpP and fapR involved in fatty acid biosynthesis/metabolism and murE and pbpB involved in peptidoglycan biosynthesis was assessed by RT-qPCR. Transcription of murE, pbpB, accA, fapR, prfA, sigB, inlA and lmo2672 was not affected. On the contrary, downregulation of hly and inlJ was observed for all strains. Moreover, upregulation of acpP and downregulation of plcA, plcB, inlB, inlC and lmo2470 were observed according to the strain. The increased amount of lemongrass essential oil affected significantly the expression of acpP, hly and inlJ . Highlights: The antimicrobial effect of lemongrass essential oil was strain dependent. No effect on murE, pbpB, accA, fapR, prfA, sigB, inlA and lmo2672 transcription. Regulation of acpP, hly, plcA, plcB, inlB, inlC, inlJ and lmo2470 was strain and dose dependent.